Penerapan Speed Reading untuk Meningkatkan Hasil Membaca Kelas V SD 53 Pabbambaeng Kabupaten Bulukumba - Sitti Jauhar; Muhammad Amran; Andi Nurul Azizah (STKIP Andi Matappa Pangkep, 2023)
The problem this research is the low results of learning read students. The formulation the problem in this study, can tapplication the speed reading method improve reading learning outcomes fifth grade students SDN 53 Pabbambaeng, Kindang District, Bulukumba Regency? The purpose this research is find out whether the application speed reading method can improve reading learning outcomes for fifth grade students at SDN 53 Pabbambaeng, Kindang District, Bulukumba Regency. This research approach is descriptive qualitative approach. This type of research is Classroom Action Research. The focus this research is 1) Application of the speed reading method, 2) Student learning outcomes. The subjects in this study were students class V at SDN 53 Pabbambaeng. The subjects this study were 32 students consisting 19 girls and 13 boys and 1 teacher. Data collection techniques using observation and tests and documentation. Data analysis techniques this study are data reduction, data description and conclusion. The results showed that there was increase. Cycle I achieved qualification Enough (C) and cycle II achieved the qualification Good (B). The conclusion this study is that applying the speed reading method can improve reading learning outcomes for fifth grade students at SDN 53 Pabbambaeng, Kindang District, Bulukumba Regency.